PENGARUH KINERJA KEUANGAN, GOOD CORPORATE GOVERNANCE (GCG), DAN MEDIA EXPOSURE TERHADAP ISLAMIC SOCIAL REPORTING (ISR) (Studi Empiris Pada Perusahaan yang Terdaftar di JII Tahun 2016-2018) - Khasanah Nur; Indrawati Novita; Azhar Al (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
Islamic Social Reporting is social reporting that does not involve holistic expectations from the community regarding the role of the company but also on a spiritual perspective. This study aims to determine the effect of return on assets (ROA), capital adequacy ratio (CAR), corporate governance, and media exposure to the extent of Islamic social reporting disclosure. To measure the level of Islamic social reporting, use a checklist that has been developed based on relevant regulations and previous research. This study uses purposive sampling from companies registered in the Jakarta Islamic Index (JII) in 2016-2018. There are 42 companies that meet the criteria as a research sample. The results of this study indicate that return on assets (ROA) has a negative effect on Islamic social reporting (ISR), while capital adequacy ratio (CAR) and media exposure have a significant effect on Islamic social reporting (ISR) and the commentary board does not significantly influence Islamic social reporting. reporting (ISR).Keywords: Islamic social reporting, return on assets (ROA), capital adequacy ratio (CAR), board of commissioners, and media exposure